Research on Legitimacy Building and Governance of Transportation Service Platform Ecosystem Based on Three-Party Evolutionary Game - Qiaohong Pan; Wenping Luo; Zongyuan Liu; Mengmeng Luan (SAGE Open)
In recent years, the legitimacy issue has been considered an important challenge for digital service platform ecosystem sustainability. Accordingly, how to govern digital service platforms has been a significant research topic. Based on the transportation service platform ecosystem, this study establishes a three-party evolutionary game model considering strategies of government, platforms, and suppliers, and analyzes the corresponding governance mechanisms. The results show that the strategic choices of the government, platforms, and providers are interdependent. High tax rates, penalties, and social reputation are important influences that drive platforms and suppliers to actively build legitimacy. Moreover, the platform’s subsidies and penalties also influence the choice of provider strategies. This paper proposes that the government can actively regulate platforms which in turn promotes the platform management participants. Therefore, this study contributes to digital service platform ecosystem development and government policies.